Potentiality of Underutilized Crop Dioscorea Spp.: A Source of Nutraceutical - Jahan, FN; Rahim, MA; Bokhtiar, SM; Samanta, AK (SAARC Journal of Agriculture, 2020)
Good Health and Well-being is one of the important goals in the current decade of twenty first century. The people of current generation prefer the consumption of plant sourced bioactive molecules over the modern medicines because the former has no side effects and residue free. In order to mitigate the food requirement of growing global population during the previous century, the green revolution technologies focused on fewer crops leading to negligence of several important crops; popularly known as underutilized or neglected crops. In the list of underutilized crops, Dioscorea spp. occupies significant niche as it is rich in several phytochemicals and could be grown under multiple stress conditions faced by the modern agricultural practices. Besides, it has been known as prominent member under age old practices of “traditional health care system” to treat several malaises of human being during the early date of civilization. The tubers and bulbils of the Dioscorea spp. are rich in saponins, tannin, flavonoids, sterols, polyphenols, and glycosides in addition to its higher contents of basic essential nutrients such as protein, carbohydrates, vitamins, minerals etc. Further, its tubers are staple food for indigenous people of several Asian and African countries. Therefore, the Dioscorea spp. signifies as an important crop both to the next generation population as well as underprivileged class of people in the coming decade for good health wellbeing and food security. SAARC J. Agri., 17(2): 1-13 (2019)